2015
DOI: 10.1093/treephys/tpv103
|View full text |Cite
|
Sign up to set email alerts
|

Time lags between crown and basal sap flows in tropical lianas and co-occurring trees

Abstract: Water storage in the stems of woody plants contributes to their responses to short-term water shortages. To estimate the contribution of water storage to the daily water budget of trees, time lags of sap flow between different positions of trunk are used as a proxy of stem water storage. In lianas, another large group of woody species, it has rarely been studied whether stored water functions in their daily water use, despite their increasing roles in the carbon and water dynamics of tropical forests caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
2
11
1
Order By: Relevance
“…; Chen et al . , ). Tropical trees differ in the size of their internal water storage, with some large trees providing substantial amounts of water to the transpiration stream; for example, a study of canopy trees in Panama found that the amount of water withdrawn from stem water storage and used to replace transpirational water losses range from 4 kg day −1 to 54 kg day −1 daily, depending on the main stem size, representing 9–15% of a tree's total daily water loss (Goldstein et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Chen et al . , ). Tropical trees differ in the size of their internal water storage, with some large trees providing substantial amounts of water to the transpiration stream; for example, a study of canopy trees in Panama found that the amount of water withdrawn from stem water storage and used to replace transpirational water losses range from 4 kg day −1 to 54 kg day −1 daily, depending on the main stem size, representing 9–15% of a tree's total daily water loss (Goldstein et al .…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal regulation may be particularly important for lianas compared with their host trees, because lianas have a higher proportion of exposed leaves at the top of the canopy, where transpirational demand is higher (Putz ), and their internal stem water storage is comparatively small (Chen et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that wood density of lianas is, on average, lower than that of trees (Chen et al., ; Zhu & Cao, ), being comparable to wood density of tree species of secondary forest (Putz, ). Wood density was found to be negatively related to water conductance in lianas (Chen et al., ), as was recorded for trees. Kitajima, Cordero, and Wright () found that mortality was greater at lower wood densities for saplings of trees and of lianas in a Neotropical lowland community.…”
Section: Introductionmentioning
confidence: 98%
“…Cavitation of the vasculature system can be countered by small‐diameter vessels with thick walls (Hacke, Sperry, Pockman, Davis, & McCulloh, ), resulting in greater wood density. While there are extensive global databases of wood density of trees (Chave et al., ; Zanne et al., ), for lianas, data are restricted to a few local studies (Chen et al., ; Kusumoto, Enoki, & Kubota, ; Putz, ; Zhu & Cao, ), even though lianas can contribute up to 25% of stems and species numbers in tropical forests (Schnitzer & Bongers, ).…”
Section: Introductionmentioning
confidence: 99%